2019
DOI: 10.1002/ccd.28319
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve replacement in patients with preexisting liver disease: Transfemoral approach with favorable survival

Abstract: IntroductionThe treatment of aortic stenosis has been revolutionized by transcatheter aortic valve replacement (TAVR), but the experience in patients with liver disease is limited. To address this open question, we report the outcome of patients with liver disease undergoing surgical aortic valve replacement (SAVR), transapical (TA), and transfemoral (TF) TAVR.Methods and ResultsBetween January 2004 and August 2016, 4,394 patients received aortic valve replacement at our institution. We identified 85 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Though TAVR is an appealing alternative for high risk surgical patients, 19‐22 some studies suggest patients with ESLD and ESRD have higher mortality rates post‐TAVR when compared with patients without these comorbidities. Previous studies in patients with cirrhosis who underwent TAVR demonstrated in‐hospital mortality rates between 9 and 36%, and 1 year mortality rates between 36 and 67% 10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though TAVR is an appealing alternative for high risk surgical patients, 19‐22 some studies suggest patients with ESLD and ESRD have higher mortality rates post‐TAVR when compared with patients without these comorbidities. Previous studies in patients with cirrhosis who underwent TAVR demonstrated in‐hospital mortality rates between 9 and 36%, and 1 year mortality rates between 36 and 67% 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ESLD and ESRD, TAVR has emerged as a potential alternative to surgery, 1,6-8,13,19-21 however, there remains few studies evaluating clinical and echocardiographic outcomes after TAVR in patients pretransplant with ESLD and ESRD. [12][13][14] Though TAVR is an appealing alternative for high risk surgical patients, [19][20][21][22] cirrhosis who underwent TAVR demonstrated in-hospital mortality rates between 9 and 36%, and 1 year mortality rates between 36 and 67%. 10,11 Comparatively, this study had no in hospital deaths for the 15 patients with cirrhosis and only a 7.1% mortality rate at 1-year.…”
Section: Echocardiographic Findingsmentioning
confidence: 99%
“… 7 , 8 , 9 However, liver function is underappreciated, with a few studies focusing on liver function only in patients with pre‐existing liver diseases. 10 , 11 , 12 , 13 Despite many studies emphasizing the prognostic value of the combination of renal and liver function on varied types of cardiac pathologies, 14 , 15 , 16 , 17 , 18 , 19 , 20 there is a paucity of data on TAVI. Moreover, it remains to be seen which part of patients are more likely to derive hepatorenal function improvement from TAVI, and how this benefit influences intermediate‐term mortality.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] However, liver function is underappreciated, with a few studies focusing on liver function only in patients with pre-existing liver diseases. [10][11][12][13] Despite many studies emphasizing the prognostic value of the combination of renal and liver function on varied types of cardiac pathologies, [14][15][16][17][18][19][20] there is a paucity of data on TAVI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation